1995
DOI: 10.1302/0301-620x.77b3.7744919
|View full text |Cite
|
Sign up to set email alerts
|

Roentgen stereophotogrammetric analysis as a predictor of mechanical loosening of knee prostheses

Abstract: The tibial components in 143 patients with total knee replacements performed before 1988 were assessed for micromotion using roentgen stereophotogrammetric analysis (RSA) over a period of 13 years. The fixation of the prostheses remained clinically sound in all cases, although revision had been required for other reasons in seven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
502
3
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(524 citation statements)
references
References 32 publications
16
502
3
1
Order By: Relevance
“…We found that early micromotion measured with RSA increased the risk of clinical failure, consistent with previous studies [4,13,14,18,19,21,26]. However, the total mean stem subsidence for the Spectron EF Primary stem at 2 years did not exceed the threshold of 0.15 mm suggested by van der Voort et al [4,13,26] despite the fact that the 10-year stem survival rate was below 95%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that early micromotion measured with RSA increased the risk of clinical failure, consistent with previous studies [4,13,14,18,19,21,26]. However, the total mean stem subsidence for the Spectron EF Primary stem at 2 years did not exceed the threshold of 0.15 mm suggested by van der Voort et al [4,13,26] despite the fact that the 10-year stem survival rate was below 95%.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have established the ability of radiostereometry (RSA) to predict later failure of hip [4,13,14,18,26] and knee [19,21] prostheses. Measurement of early implant migration performed with the high-resolution RSA has therefore been recommended as an important part of a stepwise introduction of new implants [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the threedimensional motion of the prosthetic marker, which moves the most and indicates the magnitude of the motion. Our results indicated that the all-polyethylene component has a lower MTPM and therefore the risk of revision for aseptic loosening is less in comparison with the metal-backed component [43].…”
Section: Discussionmentioning
confidence: 64%
“…The early fixation of total joint replacements also depends on a fracture-type response in metaphyseal bone. Increased bone formation at early stages in the healing or incorporation process might provide a better long-term prognosis due to the correlation between improved early fixation and reduced risk of late loosening [1].…”
Section: Introductionmentioning
confidence: 99%